2013
DOI: 10.1142/s0219649213500287
|View full text |Cite
|
Sign up to set email alerts
|

Strategic Uncertainty and Firm Performance: The Mediating Role of Competitive Intelligence Practices

Abstract: This study aims to identify the strategic roles of competitive intelligence and to examine the mediating effect of competitive intelligence practices on the relationship between perceived strategic uncertainty and firm performance. Data are collected from 123 public listed companies in Malaysia using mail questionnaire survey. The study highlights the essential role of competitive intelligence in supporting strategic decision making and strategic planning as well as in identifying opportunities and threats. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 51 publications
0
5
0
1
Order By: Relevance
“…Numerous studies stress the value CI provides in improved decision-making and strategy (Yap and Sapuan, 2013), while empirical research has addressed the CI process and firm context. Yet, little to no research has brought this information together to build a conceptual model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies stress the value CI provides in improved decision-making and strategy (Yap and Sapuan, 2013), while empirical research has addressed the CI process and firm context. Yet, little to no research has brought this information together to build a conceptual model.…”
Section: Discussionmentioning
confidence: 99%
“…While, Dishman and Calof (2008) stated infrastructure aids "the effectiveness as well as the efficacy of the intelligence effort within the firm" (p. 779). Yap and Sapuan (2013) noted its benefits: [to] systematically conduct CI activities is seen to be crucial in making effective business decisions and to help business to be more attuned to changes in the business environment" (p. 1).…”
Section: Firm Context and The Competitive Intelligence Processmentioning
confidence: 99%
“…This points toward the ability of CI to encourage strategic thinking and stimulate dialogue with decision-makers (Gilad, 2016); therefore, organised CI plays a critical role in corporate strategy (Colakoglu, 2011). Previous research from Yap et al (2013a) indicated that CI is central to supporting strategic decision-making and planning along with identifying opportunities and threats.…”
Section: Strategy Managementmentioning
confidence: 99%
“…Concurring, Rashid (2011), andYap et al (2013b) found that more than half of the surveyed organisations had a formal CI unit in the marketing, market research, or corporate planning departments. Furthermore, their study revealed that these units had been in place for 5 to 9 years, with an average of 2 to 5 full-time individuals in charge of CI activities.…”
Section: Structure and Processmentioning
confidence: 99%
“…Mientras que las grandes empresas han ido integrando la IC en el desarrollo estratégico, las PYMEs se limitan a la realización de la vigilancia de los mercados y la competencia (J. R. . Se identifica que las PYMEs con orientación global y estrategias de diferenciación tienen incorporan más las prácticas de IC y monitorización del entorno de manera más efectiva y formalizada (S. Debido a ello las PYMEs realizan actividades IC de manera fundamentalmente informal (Ching Seng Yap & Abdul Rashid, 2011), y su prácticas difieren sustancialmente de las de las grandes empresas..…”
Section: Desafíos De La Ic Efectiva En Las Pymesunclassified